Aspectos da representação temática pela indexação de livros: análise de Assunto e suas concepções na diversificação de áreas do conhecimento em bibliotecas dos Institutos Federais de Educação, Ciência e Tecnologia (IF's) - Sousa, Brisa Pozzi de [UNESP] (2012)
The thematic representation of information, aimed at providing documentary information trough on-line catalogs of libraries, has required the area of Information Treatment and Organization the development of theoretical and instrumental subsidies to assist in analysis, synthesis and representation of the documentary contents, seeking contributions for both theoretical sedimentation of Information Science, and to promote the professional practice of librarians. The intention of researching the process of subject analysis in indexing arises from the need for empirical work in this field, once many difficulties surround the area, and perceives a small number of investigative. It is intended to contribute to the Information Treatment, both as a research phase of the sphere thematic, as for professional practice, showing how the data collected and the results can help proposals to be explored in future research. In this context, it is proposed an investigation into the thematic representation of books by catalogers during subject analysis in cataloging, from the content-oriented and requirements-oriented conceptions, in order to produce the documentary information, in catalogs of university libraries. By means of bibliographic exploratory investigation into field, with qualitative approach, this research aims to contribute to the indexer can refer more attention to the thematic representation of the document, expanding their outlook on the importance of the process of subject analysis. The results indicate that for the preparation of thematic representation in the subject analysis for indexing, which result in the documentary information in the catalogs, it is important to note the explicit and implicit information in the document... (Complete abstract click electronic access below)